Total-to-HDL Cholesterol Ratio and Visceral Adiposity Index Correlation in Type Two Diabetics with or without Ischemic Stroke - Karina Rahma Meidiarti; Phey Liana; Swanny Swanny; Tungki Pratama Umar (Majalah Kedokteran Andalas, 2021)
Objective: The study aims to analyze clinical and laboratory data differences, also the correlation of Visceral Adiposity Index (VAI) with other observed parameters in type 2 diabetics with or without ischemic stroke. Methods: This study was conducted as analytic observational study with cross-sectional design. Clinical data were directly collected from patients, followed by laboratory data collection. There was a comparison (Mann-Whitney or independent T-tests) and correlation analysis (Pearson or Spearman). Results: In the ischemic stroke group, the total-to-HDL cholesterol ratio and VAI were significantly higher (p=0.033 and 0.002, respectively) than the non-ischemic stroke group. The total-to-HDL cholesterol ratio and VAI had a significant correlation (p<0.001). Clinical (WC and VAI) and laboratory data (total cholesterol, triglyceride, LDL-C, and total-to-HDL cholesterol ratio) differ significantly in type 2 diabetics with or without ischemic stroke. Conclusion: In both diabetes groups, with or without ischemic stroke, there was a significant correlation between VAI and the total-to-HDL cholesterol ratio.